2010
DOI: 10.1161/hypertensionaha.109.149146
|View full text |Cite
|
Sign up to set email alerts
|

Oral Intake of Rosiglitazone Promotes a Central Antihypertensive Effect Via Upregulation of Peroxisome Proliferator-Activated Receptor-γ and Alleviation of Oxidative Stress in Rostral Ventrolateral Medulla of Spontaneously Hypertensive Rats

Abstract: Abstract-Rosiglitazone, a synthetic ligand of transcription factor peroxisome proliferator-activated receptor-␥ (PPAR-␥), possesses a blood pressure-lowering effect beyond insulin sensitizing and glucose lowering. Oxidative stress in rostral ventrolateral medulla (RVLM), where sympathetic premotor neurons for the maintenance of neurogenic vasomotor tone are located, contributes to neural mechanisms of hypertension. Activation of PPAR-␥ protects against oxidative stress in RVLM by upregulation of mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 57 publications
4
57
0
Order By: Relevance
“…[37][38][39] In terms of the agonist activity of peroxisome proliferator-activated receptor (PPAR)-g, a previous study suggested that orally administered rosiglitazone, a PPAR-g agonist, promotes a central antihypertensive effect via upregulation of PPAR-g and alleviation of oxidative stress in the RVLM of SHR. 40 Although both TLM and CAN function as partial agonists of PPAR-g, only TLM achieves this effect at therapeutic doses. 41 Further studies are necessary to investigate the differences in central effects elicited by the various ARBs in terms of efficacy, inverse agonist activity and PPAR-g agonist activity.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] In terms of the agonist activity of peroxisome proliferator-activated receptor (PPAR)-g, a previous study suggested that orally administered rosiglitazone, a PPAR-g agonist, promotes a central antihypertensive effect via upregulation of PPAR-g and alleviation of oxidative stress in the RVLM of SHR. 40 Although both TLM and CAN function as partial agonists of PPAR-g, only TLM achieves this effect at therapeutic doses. 41 Further studies are necessary to investigate the differences in central effects elicited by the various ARBs in terms of efficacy, inverse agonist activity and PPAR-g agonist activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Chan et al (22) suggested that transcriptional upregulation of mitochondrial uncoupling protein 2 (UCP2) in response to an increase in superoxide plays an active role in the feedback regulation of ROS production in the RVLM (22). Furthermore, oral treatment with rosiglitazone enhances a central antihypertensive effect via an upregulation of peroxisome proliferator-activated receptor-␥ (PPAR-␥) and reduced oxidative stress in the RVLM of SHR (23). Stimulation of PPAR-␥ results in the upregulation of UCP2, thereby reducing oxidative stress.…”
Section: Sources Of Ros Generation In the Brain Stemmentioning
confidence: 99%
“…A third group of animals received microinjection bilaterally into RVLM, nucleus tractus solitarii (NTS), or hypothalamic paraventricular nucleus (PVN) of a lentiviral vector (Lv) carrying small hairpin RNA (shRNA) on week 6 to silence protein inhibitor of neuronal NOS (nNOS; PIN; Lv-PIN shRNA, 1×10 6 pfu/80 nL). The dose of test agents used was adopted from previous studies 12,22,23 or determined in the pilot study. In each experimental group, the levels of fasting plasma glucose, insulin, and triglycerides were determined before, every week, and at the end of 8 weeks of ND or HFD.…”
Section: Methodsmentioning
confidence: 99%